MENATA REGULASI PEGADAIAN SYARIAH (UPAYA MENERAPKAN AL-MAQASID DAN MEMINIMALKAN KESENJANGAN SOSIAL) - Iiz Izmuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2016)
This study aims to prove that legislation or government regulation (No. 103 of 2000) relating to pawnshops still have not touched the side of shari'a, thus because its existence is intended for business purposes and does not touch the social side. Whereas the original purpose of al-Rahn contract is for social purposes. Changes in the transaction purpose of social objectives into the business transaction will result in social problems. The research method with a theoretical framework Maqasid al-Shariah that seen from the legal perspective (Islam), ethics, and the unity will be linked with the Fatwa No. 25 / DSN-MUI / III / 2002 concerning Rahn, DSN-MUI No. 26 / DSN-MUI / III / 2002 concerning Gold Rahn and DSN No. 68 / DSN-MUI / III / 2008 concerning Rahn tasjily as a reference of the technical implementation in implementing the Islamic pawnshop Organization products. The study concluded that the presence of the Islamic pawnshop just touches the side of the law, but the ethics and the unity is still neglected, for example, the issue of justice and social inequality and this paper describes how should the rules applied by social institutions so that the application of al-Rahn can be applied in its tracks, to reduce social- economic inequalities. Penelitian ini betujuan ingin membuktikan bahwa Undang-undang atau Peraturan Pemerintah (Nomor 103 tahun 2000) yang berkaitan dengan pegadaian masih belum menyentuh sisi syariah, hal demikian dikarenakan keberadaanya diperuntukan untuk tujuan bisnis belaka dan tidak menyentuh sisi sosialnya. Padahal tujuan awal disyariatkannya akad al-rahn adalah untuk tujuan sosial. Perubahan tujuan transaksi dari tujuan sosial merubah dengan transaksi bisnis akan berakibat pada masalah sosial. Metode penelitian dengan kerangka teori Maqasid al-Shariah yang dilihat sisi hukum (Islam), etika, dan tauhid akan dihubungkan dengan Fatwa No. 25/DSN-MUI/III/2002 tentang Rahn, DSN-MUI No. 26/DSN-MUI/III/2002 tentang Rahn Emas dan Fatwa DSN No. 68/DSN-MUI/III/2008 tentang rahn tasjily sebagai rujukan dari pelaksanaan teknis dalam melaksanakan produk Lembaga Pegadaian Syariah. Penelitian ini menyimpulkan bahwa keberadaan Pegadaian Syariah hanya menyentuh sisi hukum saja, namun sisi etika dan tauhid masih terabaikan, misalnya masalah keadilan dan kesenjangan sosial dan tulisan ini menjelaskan bagaimana seharusnya peraturan-pertauran yang diterapkan lembaga sosial sehingga penerapan al-rahn dapat diterapkan di jalurnya yaitu untuk mengurangi kesenjangan sosial-eonomi